DISCOURSE ANALYSIS AS THE STRATEGY OF PHILOSOPHICAL METHODOLOGY IN MODERN HUMANITARIAN SCIENCES - Комісар, Л. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The research concentrated on questions of ontology of discourse and universalization of this concept which open a possibility for understanding a significance of the philosophical method of discourse analysis for modern humanities.